2017
DOI: 10.1007/s10803-017-3386-8
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Parent Learning to Promote Social Communication for Toddlers with Autism: Effects from a Randomized Controlled Trial

Abstract: A randomized controlled trial was conducted to evaluate effects of the Joint Attention Mediated Learning (JAML) intervention. Toddlers with autism spectrum disorders (ASD) aged 16-30 months (n = 144) were randomized to intervention and community control conditions. Parents, who participated in 32 weekly home-based sessions, followed a mediated learning process to target preverbal social communication outcomes (social visual synchrony, reciprocity, and responding and initiating forms of joint attention) through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(138 citation statements)
references
References 43 publications
1
135
0
Order By: Relevance
“…Two studies examined how a child's autism severity influenced treatment effects, and results were conflicting. Pajareya et al (2012) found that the less severe the impairments or the higher the level of overall performance of the child prior to intervention, the more likely they were to have positive gains from the DSP intervention.In contrast, Schertz et al (2018) found that more positive changes in responding to joint attention occurred for the children with more severe autism. However, treatment effects for following faces, turn taking, and initiating joint attention were not influenced by autism severity.…”
Section: Factors Influencing Dsp Intervention Effectsmentioning
confidence: 64%
See 3 more Smart Citations
“…Two studies examined how a child's autism severity influenced treatment effects, and results were conflicting. Pajareya et al (2012) found that the less severe the impairments or the higher the level of overall performance of the child prior to intervention, the more likely they were to have positive gains from the DSP intervention.In contrast, Schertz et al (2018) found that more positive changes in responding to joint attention occurred for the children with more severe autism. However, treatment effects for following faces, turn taking, and initiating joint attention were not influenced by autism severity.…”
Section: Factors Influencing Dsp Intervention Effectsmentioning
confidence: 64%
“…therapist's fidelity to delivering treatment, fidelity of parent training, and fidelity of parent use of DSP strategies; Roberts & Kaiser, 2011). Within our review, although many studies reported use of fidelity measures, only one (Schertz et al, 2018) looked at fidelity at more than one level of implementation (i.e. clinician and caregiver).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this line of studies, from 2009, seventy-nine other studies were also published [15-17,19-24-26,27,29-32,34-45,47-77,79,80,83,84,88-94,96,98-102,104-107], and fourteen studies were published from 1994 to 2009 [18,25,28,33,46,78,81,82,[85][86][87]95,97,103]. Fortyone of the above mentioned studies were conducted in USA [18,19,21,23,24,30,32,34,37,38,[42][43][44][45][46][47]49,50,[53][54][55][56]60,61,63,[74][75][76][77][78][79][83][84][85][86][87][88]…”
Section: Resultsmentioning
confidence: 99%